Multiple breath washout testing in adults with pulmonary disease and healthy controls - can fewer measurements eventually be more? - Trinkmann, Frederik; Götzmann, Johannes; Saur, Daniel; Roth, Katharina; Stach-Jablonski, Ksenija; Borggrefe, Martin; Saur, Joachim; Akın, Ibrahim; Michels-Zetsche, Julia D. (BMC pulmonary medicine, 2017)
Multiple breath washout (MBW) became a valuable research tool assessing ventilation heterogeneity. However, routine clinical application still faces several challenges. Deriving MBW parameters from three technically acceptable measurements according to current recommendations prolongs test times. We therefore aimed to evaluate reporting only duplicate measurements in healthy adults and pulmonary disease.